Bimbingan Konseling Islam untuk Mengatasi Kenakalan Remaja - Azizah, Ulfatun (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
Adolescence is a time of many changes both physical, spiritual, mind, so at this time teenagers experience a lot of adolescent emotional turmoil and adolescent problems in general are caused by social role conflict. On the one hand he already wants to be independent as an adult, on the other hand he still has to continue to follow the wishes of parents. The emotional turmoil caused his psychological condition to be unstable due to the unstable condition which also caused the teenagers to be very easily influenced by the surrounding environment. Problems that arise among adolescents that can be categorized as serious problems include the problem of juvenile delinquency, given that adolescents are an age group that is expected to be the next generation of successors in the future. Islamic counseling guidance aims to help individuals realize themselves into full human beings to achieve the happiness of life in the world and in the hereafter in accordance with Islamic law.